Excess dietary leucine in diets for growing pigs reduces growth performance, biological value of protein, protein retention, and serotonin synthesis(1) - Kwon, Woong B (J Anim Sci, 2019)
An experiment was conducted to test the hypothesis that excess dietary Leu affects metabolism of branched-chain amino acids (BCAA) in growing pigs. Forty barrows (initial body weight [BW]: 30.0 ± 2.7 kg) were housed individually in metabolism crates and allotted to 5 dietary treatments (8 replicates per treatment) in a randomized complete block design. The 5 diets were based on identical quantities of corn, soybean meal, wheat, and barley and designed to contain 100%, 150%, 200%, 250%, or 300% of the requirement for standardized ileal digestible Leu. Initial and final (day 15) BW of pigs were recorded. Daily feed consumption was also recorded. Urine and fecal samples were collected for 5 d following 7 d of adaptation to the diets. At the end of the experiment, blood and tissue samples were collected to analyze plasma urea N (PUN), plasma and hypothalamic serotonin, tissue BCAA, serum and tissue branched-chain α-keto acids, and messenger ribonucleic acid abundance of genes involved in BCAA metabolism. Results indicated that acid detergent fiber, average daily feed intake, and gain-to-feed ratio decreased (linear, P < 0.05) as dietary Leu increased. A trend (linear, P = 0.082) for decreased N retention and decreased (linear, P < 0.05) biological value of dietary protein was also observed, and PUN increased (linear, P < 0.05) as dietary Leu increased. A quadratic reduction (P < 0.05) in plasma serotonin and a linear reduction (P < 0.05) in hypothalamic serotonin were observed with increasing dietary Leu. Concentrations of BCAA in liver increased (linear, P < 0.001), whereas concentrations of BCAA in skeletal muscle decreased (linear, P < 0.05) as dietary Leu increased. Concentration of α-ketoisovalerate was reduced (linear and quadratic, P < 0.001) in liver, skeletal muscle, and serum, and α-keto-β-methylvalerate was reduced (linear, P < 0.001; quadratic, P < 0.001) in skeletal muscle and serum. In contrast, α-keto isocaproate increased (linear, P < 0.05) in liver and skeletal muscle and also in serum (linear and quadratic, P < 0.001) with increasing dietary Leu. Expression of mitochondrial BCAA transaminase and of the E1α subunit of branched-chain α-keto acid dehydrogenase increased (linear, P < 0.05) in skeletal muscle as dietary Leu increased. In conclusion, excess dietary Leu impaired growth performance and nitrogen retention, which is likely a result of increased catabolism of Ile and Val, which in turn reduces availability of these amino acids resulting in reduced protein retention, and excess dietary Leu also reduced hypothalamic serotonin synthesis.